The challenges of empowering Kuwaiti women in light of the current political changes - Al Ajmi, Nouf Nashmi Hassan (Journal of Humanities & Social Sciences, 2017)
This study was conducted under the title of "The Challenges of the Kuwaiti women’s empowerment in the light of the current political changes", which aims to clarify the women’s empowerment issue in the State of Kuwait, through the identification of the role of the State of Kuwait in the empowerment of women at all levels and to identify the most prominent problems that facing women in the Kuwaiti state. To achieve the objective of this study the researcher used the descriptive approach, by reviewing previous researches and studies relevant to this study topic. At the end of the study the researcher summarized that the main obstacles that stand in front of the Kuwaiti women’s empowerment is the customs and traditions of the wrong understanding of religion, as well as the emergence of political empowerment in particular as one of the most common types of empowerment that lacks Kuwaiti women. Therefore, the researcher has worked on finding a set of recommendations designed to increase the empowerment of women, including to conduct several relevant seminars that illustrate the essential role of women, in addition to explain the Islamic view towards women’s participation in various critical positions.